2019
DOI: 10.1111/jicd.12434
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of cordless sonic or ultrasonic devices on Enterococcus faecalis‐infected root canals

Abstract: Aim The aim of the present study was to evaluate the immediate and residual antimicrobial activity of cordless sonic or ultrasonic devices on Enterococcus faecalis (E faecalis)‐infected teeth. Methods A total of 140 single‐rooted extracted teeth with E faecalis were grouped as follows (N = 15): conventional syringe irrigation with 3% sodium hypochlorite activated by ultrasonic device (group 1) or cordless ultrasonic device (group 2), EndoActivator (group 3) or without activation (group 4), conventional syringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…However, the cleaning ability of all three final irrigation protocols tested in the present study was similar, with no significant statistical differences ( p > 0.05) between them. These results agreed with previous studies that have confirmed the efficiency of the EndoUltra device in the eradication of bacterial biofilms [ 22 , 33 ]. The performance of PUI depends upon the acoustic streaming and cavitation taking place.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the cleaning ability of all three final irrigation protocols tested in the present study was similar, with no significant statistical differences ( p > 0.05) between them. These results agreed with previous studies that have confirmed the efficiency of the EndoUltra device in the eradication of bacterial biofilms [ 22 , 33 ]. The performance of PUI depends upon the acoustic streaming and cavitation taking place.…”
Section: Discussionsupporting
confidence: 93%
“…This device claimed to improve the cleaning and disinfection of a root canal system, facilitating the upward debris removal, eliminating the biofilm and the smear layer from the canal walls at a higher rate, and making microorganisms more sensitive to NaOCl due to its temporary action on the bacterial cell wall and cytoplasmic membrane. However, there are few reported studies on the efficiency of this ultrasonic device in root canal disinfection [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Endoactivator (Dentsply Sirona, Ballaigues, Switzerland) is a further example of a battery-operated sonic cordless device, coupled with no-cutting polymer tips, which do not cut root dentin and are available in three sizes (15.02, 25.04, 35.04). It can be used at three different speeds, 10,000, 6000, and 2000 cycles per minute, generating a 160/190 Hz frequency [ 13 ] to improve the final irrigation protocol. Its design allows for the safe activation of intracanal irrigants, as well as irrigation inside curved root canals.…”
Section: Introductionmentioning
confidence: 99%
“…The EndoUltra (Micromega, Besançon, France) was the first cordless ultrasonic instrument generating a 40,000 Hz frequency. This device presents a rechargeable lithium ion battery and a single 15.02 stainless steel tip [ 13 ]. However, its rigid and nonflexible tip, especially in the curved root canals in contact with the dentinal walls, could create an unintentional intracanal ledge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the vapour lock effect, caused by trapped air bubbles in the canal, inhibits apical irrigation [4]. By overcoming CNI accessibility issues [5], ultrasonic [6] and sonic oscillation [7] and laser-based agitation techniques [8] effectively spread the irrigant throughout the root canal system. Specifically, laser-activated irrigation (LAI) successfully flushes hard-to-reach areas [9].…”
Section: Introductionmentioning
confidence: 99%